Amoxicillin Plus Metronidazole Therapy for Patients with Periodontitis and Type 2 Diabetes: A 2-year Randomized Controlled Trial. (July 2016) - Tamashiro, N.S.; Duarte, P.M.; Miranda, T.S.; Maciel, S.S.; Figueiredo, L.C.; Faveri, M.; Feres, M.
The aim of this study was to assess the changes occurring in subgingival biofilm composition and in the periodontal clinical parameters of subjects with periodontitis and type 2 diabetes mellitus (DM) treated by means of scaling and root planing (SRP) only or combined with systemic metronidazole (MTZ) and amoxicillin (AMX). Fifty-eight subjects were randomly assigned to receive SRP only ( n = 29) or with MTZ (400 mg/thrice a day [TID]) and AMX (500 mg/TID) ( n = 29) for 14 d. Six subgingival plaque samples/subject were analyzed by checkerboard DNA–DNA hybridization for 40 bacterial species at baseline and 3 mo, 1 y, and 2 y posttherapy. At 2 y posttherapy, the antibiotic-treated group harbored lower mean proportions (5.5%) of red complex pathogens than the control group (12.1%) ( P < 0.05). The proportions of the Actinomyces species remained stable in the antibiotic group but showed a statistically significant reduction in the control group from 1 to 2 y in subjects achieving a low risk clinical profile for future disease progression (i.e., ≤4 sites with probing depth [PD] ≥5 mm). The test group also had a lower mean number of sites with PD ≥5 mm (3.5 ± 3.4) and a higher percentage of subjects reaching the low risk clinical profile (76%) than the control group (14.7 ± 13.1 and 22%, respectively) ( P < 0.05) at 2 y posttreatment. MTZ + AMX intake was the only significant predictor of subjects achieving the low risk at 2 y (odds ratio, 20.9; P = 0.0000). In conclusion, the results of this study showed that the adjunctive use of MTZ + AMX improves the microbiological and clinical outcomes of SRP in the treatment of subjects with generalized chronic periodontitis and type 2 DM up to 2 y (ClinicalTrials.gov NCT02135952).